PERANCANGAN SISTEM INFORMASI ABSENSI KARYAWAN DENGAN QR CODE BERBASIS WEB PADA PT. WATEROAM TECHNOLOGIES INDONESIA - Waruwu, Mercy Mariani; Ilmi, Miftahul (JUTEKDISI, 2025)
This study aims to design and implement a web-based employee attendance information system using QR Code technology at PT. Wateroam Technologies Indonesia. The system is designed to improve the efficiency of attendance processes, reduce the potential for administrative errors, and provide real-time attendance data management. The methods used include requirement analysis, system design, and implementation using modern web technology. The implementation results indicate that the QR Code-based attendance system offers an effective solution for faster, more accurate, and transparent attendance recording. The system enables real-time and automated attendance data management, making it easier for management to monitor employee attendance and enhancing work discipline. Additionally, the system simplifies the creation of various reports, such as daily, weekly, or monthly recaps, with flexible formats tailored to the company's needs. The data generated can also be used as a basis for performance evaluation and human resource planning, including work schedule arrangements and overtime allocation. In conclusion, the QR Codebased attendance system successfully meets the needs of PT. Wateroam Technologies for more efficient and accurate attendance management. With further development, such as integration with payroll systems and enhanced data security, the system has the potential to become a comprehensive solution for managing employee attendance and productivity